Oxford genome screen for asthma-associated traits - Cookson,WOCM; Abeçasis,GR (2001)
A genome screen for linkage of quantitative traits underlying asthma has been carried out previously by our group on 80 families sub-selected for discordant phenotypes from a general population sample. The families contained a total of 203 offspring forming 172 sib-pairs. Genotypic data for at a total of 296 markers were available. This paper describes the ascertainment, phenotypic data, and genotypic data made available for Genetic Analysis Workshop 12. © 2001 Wiley-Liss, Inc.